Implication of bisphosphonate use in the treatment of SAPHO syndrome: Case report and discussion of current literature. Issue 2 (December 2015) - Gorecki, Patricia; Stockmann, Philipp; Distler, Jörg H.W.; Wuest, Wolfgang; Schmidt, Daniela; Neukam, Friedrich Wilhelm; Nkenke, Emeka; Wehrhan, Falk
Graphical abstract: Highlights: In SAPHO syndrome patients affected structures partly derive from neural crest cells. Bisphosphonates improve SAPHO syndrome symptoms but the pathophysiology is unknown. Bisphosphonates are potentially pro-osteoblastic by influencing transcription factors. Abstract: Even though increasing knowledge is emerging about synovitis, acne, pustulosis, hyperostosis and osteitis (SAPHO) syndrome its pathogenesis remains enigmatic. Women are preferentially affected by SAPHO syndrome. Here we present the case of a 39-year-old woman suffering from this syndrome whose bone involvement was first interpreted as diffuse sclerosing osteomyelitis of the mandible. As treatment with clindamycin did not improve the symptoms, the decision was made to administer bisphosphonates intravenously. This treatment led to a rapid improvement in symptoms, which could be explained by the apparent tendency of bisphosphonates to exert a positive effect on the jaw. With this case report we attempt to offer an explanation for the influence of this group of medications on patients suffering from SAPHO syndrome with mandibular involvement.